CSR expectations and voluntary participation among employees - Bakosné Kiss, Virág Ágnes; Kiss, Kincső; Szakács, Attila; Szűcs, Róbert (Economica, 2024)
Our research aims to reveal the expectations of employees towards their organization about CSR initiatives, and also to map out what attitudes characterize them in connection with volunteerism that looks back on old traditions. With the involvement of more than 300 people in our research - mostly employees of large companies - we mapped the employee attitudes by analysing statistical and spontaneous mentions. Based on our results, it became clear that the employees consider it important that their employer also carries out socially responsible activities, and that their most important task is to achieve economic efficiency. They are also happy to participate in volunteer activities for a good cause.